Performance Evaluation of a Construction Materials Testing Laboratory in the Implementation of ISO/IEC 17025:2017 - Azhari, Firdha Aulia Ariyani; Anas, Muhammad Ridwan; Mulia , Ahmad Perwira; Hasibuan, Gina Cynthia Raphita; Mardianta, Anthoni Veery (Universitas Ibn Khaldun Bogor, 2026)
Public construction materials laboratories play a vital role in safeguarding infrastructure quality and public safety. Although ISO/IEC 17025:2017 is widely adopted as a quality management system, its actual influence on strategic performance in government laboratories is not well understood. This study evaluates the implementation of ISO/IEC 17025:2017 at a provincial government testing laboratory in North Sumatra, Indonesia, by integrating it with the Balanced Scorecard (BSC) framework. A mixed-methods approach was used involving 60 participants—30 internal personnel and 30 external users—through surveys, interviews, and direct observation. The BSC evaluation produced a performance score of 77.35%, categorized as satisfactory, with the strongest contribution from customer and financial perspectives. This study introduces an integrated evaluation framework tailored to public laboratories, bridging quality compliance with strategic governance. The results highlight the importance of aligning technical quality with institutional accountability, offering a practical pathway for improving performance and public trust in government testing services.